2017
DOI: 10.3390/ijms18122712
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical and Antimicrobial Characterization of Beeswax–Starch Food-Grade Nanoemulsions Incorporating Natural Antimicrobials

Abstract: Nanoemulsions are feasible delivery systems of lipophilic compounds, showing potential as edible coatings with enhanced functional properties. The aim of this work was to study the effect of emulsifier type (stearic acid (SA), Tween 80 (T80) or Tween 80/Span 60 (T80/S60)) and emulsification process (homogenization, ultrasound or microfluidization) on nanoemulsion formation based on oxidized corn starch, beeswax (BW) and natural antimicrobials (lauric arginate and natamycin). The response variables were physico… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 60 publications
0
4
0
1
Order By: Relevance
“…Therefore, they have gained prominent attention in the scientific community. Recent uses of beeswax-starch, jujube gum, sodium caseinate, turmeric extract, linalool, docosahexaenoic and eicosapentaenoic acid, cumin seed oil, whey protein isolate, and oils like cinnamon, lemon and anise myrtle essential oils in nanoemulsion formulations (Arredondo-Ochoa et al 2017 ; Gharibzahedi and Mohammadnabi 2017 ; Nirmal et al 2018 ; Noori et al 2018 ; Prakash et al 2019 ; Zhang et al 2019 ; Park et al 2019 ; Farshi et al 2019 ; Pongsumpun et al 2020 ) have shown high potentials in the food industry and for the general well being. They can also deliver phytochemicals and other bioactive components in the food industry (Mahmood et al 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, they have gained prominent attention in the scientific community. Recent uses of beeswax-starch, jujube gum, sodium caseinate, turmeric extract, linalool, docosahexaenoic and eicosapentaenoic acid, cumin seed oil, whey protein isolate, and oils like cinnamon, lemon and anise myrtle essential oils in nanoemulsion formulations (Arredondo-Ochoa et al 2017 ; Gharibzahedi and Mohammadnabi 2017 ; Nirmal et al 2018 ; Noori et al 2018 ; Prakash et al 2019 ; Zhang et al 2019 ; Park et al 2019 ; Farshi et al 2019 ; Pongsumpun et al 2020 ) have shown high potentials in the food industry and for the general well being. They can also deliver phytochemicals and other bioactive components in the food industry (Mahmood et al 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Son compuestos formados de un alcohol monohidroxílico de alto peso molecular esterificado con un ácido graso de cadena larga, de más de 24 carbonos; se presentan como cubiertas protectoras en los vegetales y animales; la lana y las plumas están protegidas por ceras. La cera de abeja tiene el palmitato de miricilo, un producto de color blanco cuando fresco, es una cera de grado alimenticio de uso como vehículo para medicamentos, medio de liberación lenta para medicamentos y como emulsión y base para cosméticos (Arredondo-Ochoa et al, 2017).…”
Section: Cerasunclassified
“…The mean particle diameter of FS was determined with a Zetasizer Nano-ZS laser diffractometer (Malvern Instruments, Worcestershire, UK) at 633 nm and 25 • C, equipped with a backscatter detector [34].…”
Section: Particle Sizementioning
confidence: 99%
“…Z potential (mV) was determined by phase analysis light scattering (PALS) with a Zetasizer Nano-ZS laser diffractometer (Malvern Instruments, Worcestershire, UK), which determines electrical charge at interface of droplets dispersed in aqueous phase [34].…”
Section: Z Potentialmentioning
confidence: 99%